Abraham Lincoln, will you ever give up? - Uglow, Loyd, 1952-; James, Kennon (Houston : Advance Pub., 1997)
Follows the life of the greatly admired American president, from his childhood in a log cabin to his actions in the White House.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents